PENGEMBANGAN SISTEM MONITORING KUALITAS AIR EMPANG MENGGUNAKAN MIKROKNTROLER ESP32 - Khaerun Nisa; Adi Chandra; Nurwahid Syam (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to design the Development of a Pond Water Quality Monitoring System Using the Esp32 Microcontroller in the Panyutanah hamlet shrimp pond, to implement and determine the community's response to the development of the Pond water quality monitoring system using the Esp32 microcontroller with Telegram notifications. This research uses development research methods adapted from the 4-D model (Four-D Model), which includes the stages of defining, designing, and developing. Based on the results of research on developing a pond water quality monitoring system using the Esp32 microcontroller, it can be concluded that: (1) This tool uses the Esp32 Microcontroller as a data processor, servo motor (water pump) as a place for water to enter and exit, the LCD functions to display the pH value and the temperature given by the sensor, as well as Telegram as a monitoring tool. As for testing the system used using the Black Box method. (2) From the test results it was found that the development of a pond water quality monitoring system using the Esp32 microcontroller could make it easier for shrimp farmers to know the water quality automatically.